HIDROLISIS KITOSAN MENGGUNAKAN KATALIS ASAM KLORIDA (HCl) - Irsan Adhiatama; Muhamad Zainudin; Nur Rokhati (JURNAL TEKNOLOGI KIMIA DAN INDUSTRI, 2012)
The molecular weight is an important factor in the application of chitosan. High molecular weight will restrict the use of chitosan. This research uses a chemical process with acid hydrolysis. Hydrolysis is de-polymerization to lower molecular weight that occur because of the termination of glycoside bond by reaction with water (H2O). De-polymerization of chitosan is different from other polysaccharide compounds, because its have a difficult decomposed β-bond and a cationic amine groups. Therefore, it required operating conditions and type of catalyst to produce chitosan in accordance with specifications. The purpose of this research is to obtain optimum conditions of chitosan hydrolysis process and determine the type of acid catalyst is best to produce chitosan with low molecular weight (LMWCs). Results showed that temperature, catalyst concentration, and type of catalyst greatly affect on the depolymerization of chitosan. Depolymerization effect increases with increasing temperature and catalyst concentration, characterized by reduced viscosity and molecular weight of chitosan. To produce chitosan with a molecular weight between 50-100 kDa, optimum conditions : temperature of 70 0C, hydrolysis time 120 minutes, and the concentration of Hidrochloric Acid (HCl )was 0.6 to 0.8 N.